Waiting To Be Found : Papers on Children in Care. - Briggs, Andrew (TAVI., 2012)
This book is about children in State care and its title - Waiting to be Found - is derived from an observation about such children by the child psychotherapist Hamish Canham. In one of his early papers Canham wrote that children's homes often reminded him of "station waiting rooms with children waiting to move on to their next placement and staff waiting for the next shift, or working as a residential social worker in order to get experience before moving on to do something else or further training." This book takes his comment about waiting rooms as its starting point, with each contributor b.